Air conditioning system by solid desiccant using solar or residual energy as a source of regeneration heat - Morato Lins e Silva, Juliana; Romero Ferreira, Wanyr (Seven Editora, 2023)
Energy efficiency in buildings and residences is today a primary objective for energy policy at national and international level. This article presents a review of desiccant wheel air conditioning models using solar energy or waste energy as a source of regeneration heat. The physical-mathematical modeling of the rotary desiccant dehumidifier is also presented. The advantages of using the rotary desiccant air conditioning system are discussed as it combines desiccant dehumidification and evaporative cooling technologies. What's more, it's CFC-free, uses little heat energy that can be diversified (solar energy and/or waste heat), and controls humidity and temperature separately. Recent research works suggest that new desiccant materials and their configurations have significant potential to improve the performance and reliability of the process, reducing the cost and size of the dehumidification and air conditioning system with rotary dehumidifiers, thus increasing its competitiveness in the market. DOI: 10.56238/pacfdnsv1-107